PERANAN IBU DALAM MEMPERKENALKAN KONSEP KERAGAMAN AGAMA DAN RAS (SARA) KEPADA ANAK USIA DINI - Chaeroni Chaeroni; Khoirul Anwar (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2018)
Multiculturalism and conflicts caused by SARA in Indonesia have always been a problem that attracts researchers. Many other researchers doing research on this subject, among others by using political, religious, state, and education perspectives. While this study uses another perspective, namely from the perspective of family caring, especially the role of mothers in developing the concept of diversity in childhood as an effort to prevent racial conflict.This research is a qualitative research using a grounded approach. The method used to collect data is interview and focus group discussion (FGD). This research was conducted in two sub-districts, namely Gayamsari and Genuk sub-districts.The results of this study indicate that the shift in family parenting patterns has reduced the intensity of communication between parents and children. This shift causes parents to